(untitled) (ICOERESS, 2025)
The reality of discrimination against LGBT patients in health services in Indonesia is still very strong, while health law norms emphasize the state's obligation to provide equal services to all citizens without discrimination. This study aims to analyze health services for LGBT patients from a legal perspective by highlighting the gap between legal regulations and practices in the field. The methods used are normative qualitative with a Statute Approach, Comparative Approach, and Case Approach, reinforced by a literature review from national and international journals. This study fills the gap in the lack of comparative analysis between Indonesia and other countries, particularly the United States, which already has stronger legal protection through federal regulations. The results show that LGBT patients in Indonesia often experience denial of services, especially related to HIV/AIDS, which has a negative impact on their physical and mental health. The discussion reveals that discrimination stems from a weak legal framework, social stigma, and religious interpretations that reinforce negative stereotypes. A comparison with the United States confirms that although discrimination still exists in conservative areas, regulations such as the Affordable Care Act are able to create more inclusive services. The novelty of this research lies in its presentation of an integrative perspective that combines legal, social, and religious dimensions with cross-country analysis. The study emphasizes the urgency of harmonization between sectors in realizing inclusive health services and provides recommendations for Indonesia to learn from international practices while still paying attention to the local context.